Índice simple móvil por el método de la media geométrica para acciones del mercado de la construcción y su relación tendencial con los ICCP e ICCV durante el periodo 2015-2021; Simple moving average index for construction market shares and its trends relationships with the ICCP and ICCV for the period 2015-2021 - Genjis Alberto Ossa Gonzalez; Miriam Rojas Domínguez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The purpose of this article is to observe the relationship that exists between the variation of the ICCV and ICCP with respect to the prices of the variable income shares of the construction companies listed in the Colombian Stock Exchange [BVC]. In order to make this observation, it was necessary to construct simple daily moving indices using 6 companies as a sample. The results of the previous indexes were the variables chosen to calculate by the geometric mean method the monthly index in order to identify the trend relationships that exist between our indexes and the indicators of housing construction costs and weighing. Our results show that as the variation of the geometric constructed indexes increases or decreases the minimum correspondence of the housing construction and heavy construction indexes to follow the same patterns is 64.94 %, where the most important aggregate is the one linked to the housing construction.
Keywords: F65; G12; 330; ICCP; ICCV; simple moving index; geometric mean; equity